2023
DOI: 10.1002/adma.202304123
|View full text |Cite
|
Sign up to set email alerts
|

M2 Macrophage Hybrid Membrane‐Camouflaged Targeted Biomimetic Nanosomes to Reprogram Inflammatory Microenvironment for Enhanced Enzyme‐Thermo‐Immunotherapy

Abstract: Excessive inflammatory reactions caused by uric acid deposition are the key factor leading to gout. However, clinical medications cannot simultaneously remove uric acid and eliminate inflammation. An M2 macrophage‐erythrocyte hybrid membrane‐camouflaged biomimetic nanosized liposome (USM[H]L) is engineered to deliver targeted self‐cascading bienzymes and immunomodulators to reprogram the inflammatory microenvironment in gouty rats. The cell‐membrane‐coating endow nanosomes with good immune escape and lysosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Meanwhile, the levels of proinflammatory cytokines (including IL-1β, TNF-α and IL-6) were decreased, and the levels of antiinflammatory cytokine (such as IL-10) was increased in the serum and colonic sites of RMN-treated mice, in comparison with those of the colitis group (figures 6(C) and (D)). Similarly, Chen et al reported that the M2 macrophage and red blood cell hybrid membrane-camouflaged immunomodulator methotrexate could not only effectively promote M2 macrophage polarization but also inhibit the release of inflammatory cytokines [87].…”
Section: Immune Modulation 431 Immune Suppressionmentioning
confidence: 94%
See 1 more Smart Citation
“…Meanwhile, the levels of proinflammatory cytokines (including IL-1β, TNF-α and IL-6) were decreased, and the levels of antiinflammatory cytokine (such as IL-10) was increased in the serum and colonic sites of RMN-treated mice, in comparison with those of the colitis group (figures 6(C) and (D)). Similarly, Chen et al reported that the M2 macrophage and red blood cell hybrid membrane-camouflaged immunomodulator methotrexate could not only effectively promote M2 macrophage polarization but also inhibit the release of inflammatory cytokines [87].…”
Section: Immune Modulation 431 Immune Suppressionmentioning
confidence: 94%
“…There are also studies using M2 macrophage membranes for targeted drug delivery due to their ability to home to the parent cells at inflammatory sites. Considering that, Chen et al successfully applied M2 macrophage M-NPs for inflammation-targeted therapy [87].…”
Section: Drug Deliverymentioning
confidence: 99%
“…Nanozymes have emerged as effective modulators of the TME, capable of enhancing immunotherapy through diverse mechanisms such as macrophage polarization, antigen presentation, and activation of cellular pathways. 107…”
Section: Synergistic Therapies Involving Nanozymes In Cancer Treatmentmentioning
confidence: 99%
“…Combining anti-inflammatory and immune-evasive properties of M2 macrophages, the biocompatibility and long circulation of erythrocytes may produce desirable therapeutic efficacy. Most recently, Chen et al developed a novel type of biomimetic nanosized liposome (USM[H]L, 139.2 nm, -13.1 mV) that was coated with hybrid membranes derived from M2 macrophages and erythrocytes 198 . USM[H]L were loaded with uricase and methotrexate, which could synergistically degrade uric acid, scavenge H 2 O 2 , produce photothermal effects and modulate immune responses.…”
Section: Anti-inflammatory Nanotherapeuticsmentioning
confidence: 99%
“…Upon being injected into a rat model of gouty arthritis (GA), USM[H]L showed enhanced therapeutic effects by reducing uric acid levels, ankle swelling, claw curling, inflammatory cytokines and oxidative stress, while increasing anti-inflammatory cytokines and reprogramming M1 macrophages to M2 phenotype. Notably, USM[H]L also exhibited low immunogenicity and toxicity, as well as high stability and targeting ability, compared to free uricase or other formulations, representing a promising strategy for the treatment of GA and other inflammatory-related diseases 198 .…”
Section: Anti-inflammatory Nanotherapeuticsmentioning
confidence: 99%